Tropical dry forest dynamics in the context of climate change: syntheses of drivers, gaps, and management perspectives - Siyum, Zenebe Girmay (Ecological processes, 2020)
This review attempts to synthesize the available literature on tropical dry forests and their dynamics in the context of climate change and thereby identifies possible gaps and priority areas for further research and management endeavors. Tropical dry forests (TDFs) occur in dryland environments, which are characterized by prolonged periods of dry months. They experience distinct seasonality and high inter-annual variability in climatic variables, particularly rainfall. Despite the enormous ecological and livelihood importance of TDFs, these forests are highly threatened by global changes. So far, they have received far less attention from research and development interventions as compared to the humid tropical forests. Their significance is still overlooked in many countries’ national policies. Current modeling frameworks show that drought, precipitation, and temperature are highlighted as strong drivers of tree growth and/or mortality in these forests. Well-valued and sustainably managed TDFs have the potential to contribute to climate change adaptation and mitigation, buffer against erosion and desertification, and contribute to economic development, food security, and poverty alleviation. TDFs suffer notable disregard from research and development strategies. Thus, greater awareness and appropriate policies and investments are needed at various levels to counteract the increasing vulnerability of people, forest ecosystems, and species living in these fragile ecosystems. Further research is also needed to generate knowledge on the status and significances of TDFs and their responses in the face of the changing climate so as to bring their sustainable management to the attention of policymakers and managers.